Memorandum of Understanding between the BRAC University and PATHSHALA South Asian Media Institute (2012) - BRAC University; PATHSHALA (BRAC University and PATHSHALA South Asian Media Institute, 2013)
BRACU and PATHSHALA have decided to jointly offer the Post Graduate certificate courses, namely Basic certificate course in Broadcast and Cross-media Journalism and Advanced certificate course in Broadcast and Cross-media journalism. These Joint activities will be conducted under the Agreement signed by both BRACU and PATHSHALA.